Quasi-sports games and their role in developing the socio-emotional field in a football training session (junior category) - benrdjem, ahmed; benrdjem, idris (sports creativity, 2025)
The science of sports training is considered one of the applied sciences that relies on scientific knowledge and its innovations, aiming to provide the sports coach with information, knowledge, and applications that help him achieve the best results with his players by using the best available methods, techniques, and means in a scientific manner. The coach plays a significant role in energizing the training session through the use of "quasi-sports games," which are highly important in the field of training, as they increase motivation and development of achievement in practical settings. These games can be considered as a method or a set of fun and recreational movements and activities derived from the idea and purpose of the defined game, developing physical and mental abilities in an active way, such as small games. This is because they originate from children and are inspired by traditions and social customs and can be considered a foundation for games. Quasi-sports games have various fields that assist both the coach and the trainee; on one hand, they help the trainee learn according to their abilities, and on the other hand, they assist the coach in conducting the training session in an effective and enjoyable manner, aiming to achieve and develop the desired objectives through training sessions. Among these fields that can be utilized by...The coach can achieve this when practicing quasi-sports games (the psychomotor domain, the cognitive domain, the social-emotional domain). Our focus has been on the social-emotional domain, neglecting the other domains, because it relates to the psychological and social state that contributes to the player's social development and emotional and affective balance. The player learns through playing with others and through the guidance and supervision of adults to acquire behavioral standards. It is considered one of the most important domains because the topic concerns the age group classified as cubs, which is a stage of adolescence characterized by intense emotions, potentially leading to a psychological crisis marked by suffering, conflict, frustration, and anxiety. Due to the importance of this domain during training sessions, we posed the following issue: - Do quasi-sports games play a role in developing the social-emotional domain? From this issue, we derived the following sub-questions: _ Do quasi-sports games play a role in developing a sense of responsibility? _ Do quasi-sports games play a role in developing a sense of cooperation?